Acute Sleep Deprivation Increases Serum Levels of Neuron-Specific Enolase (NSE) and S100 Calcium Binding Protein B (S-100B) in Healthy Young Men. Issue 1 (1st January 2014) - Benedict, Christian; Cedernaes, Jonathan; Giedraitis, Vilmantas; Nilsson, Emil K.; Hogenkamp, Pleunie S.; Vågesjö, Evelina; Massena, Sara; Pettersson, Ulrika; Christoffersson, Gustaf; Phillipson, Mia; Broman, Jan-Erik; Lannfelt, Lars; et al.
Abstract: Study Objectives: To investigate whether total sleep deprivation (TSD) affects circulating concentrations of neuron-specific enolase (NSE) and S100 calcium binding protein B (S-100B) in humans. These factors are usually found in the cytoplasm of neurons and glia cells. Increasing concentrations of these factors in blood may be therefore indicative for either neuronal damage, impaired blood brain barrier function, or both. In addition, amyloid β (Aβ) peptides 1–42 and 1–40 were measured in plasma to calculate their ratio. A reduced plasma ratio of Aβ peptides 1–42 to 1–40 is considered an indirect measure of increased deposition of Aβ 1–42 peptide in the brain. Design: Subjects participated in two conditions (including either 8-h of nocturnal sleep [22:30-06:30] or TSD). Fasting blood samples were drawn before and after sleep interventions (19:30 and 07:30, respectively). Setting: Sleep laboratory. Participants: 15 healthy young men. Results: TSD increased morning serum levels of NSE (P = 0.002) and S-100B (P = 0.02) by approximately 20%, compared with values obtained after a night of sleep. In contrast, the ratio of Aβ peptides 1–42 to 1–40 did not differ between the sleep interventions. Conclusions: Future studies in which both serum and cerebrospinal fluid are sampled after sleep loss should elucidate whether the increase in serum neuron-specific enolase and S100 calcium binding protein B is primarily caused by neuronal damage, impaired blood brain barrier function, or is just a consequence of increased gene expression in non-neuronal cells, such as leukocytes.